2014
DOI: 10.1063/1.4901307
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional positive column structure in a discharge tube with radius discontinuity

Abstract: The low-pressure (40 and 90 Pa) low-current (4 and 10 mA) direct current discharge in a tube with a sharp change of its radius is studied both numerically and experimentally. A fully self-consistent hybrid numerical model of a two-dimensional non-uniform positive column in neon is developed using a nonlocal approach. The model combines kinetic simulation of the electrons (under two-terms approach) and fluid description of the neon ions and permits to calculate the distribution of all plasma parameters in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The first one applies the theoretical model for the particle wake potential in collisional flowing plasmas [ 16 ], and another approach introduces the trapped ion distribution and associated dipole moment induced by external electric fields [ 18 ]. The results were then applied to the parameter space of the PK-4 facility on board ISS, using the probe measurements of the plasma parameters [ 7 , 8 , 9 , 10 ]. It was found that, in the experimental conditions, the local variations in the (free or trapped) ion charge distribution induced by weak discharge electric fields reduce significantly the repulsion between two particles, and it can be, furthermore, turned into explicit attraction at realistic interparticle distances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one applies the theoretical model for the particle wake potential in collisional flowing plasmas [ 16 ], and another approach introduces the trapped ion distribution and associated dipole moment induced by external electric fields [ 18 ]. The results were then applied to the parameter space of the PK-4 facility on board ISS, using the probe measurements of the plasma parameters [ 7 , 8 , 9 , 10 ]. It was found that, in the experimental conditions, the local variations in the (free or trapped) ion charge distribution induced by weak discharge electric fields reduce significantly the repulsion between two particles, and it can be, furthermore, turned into explicit attraction at realistic interparticle distances.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have assumed that , where the standard notations for the electron temperature , ion mass , and ion-neutral collision frequency are used. Calculations in Figure 2 and everywhere in the paper are done using the respective probe measurements of the discharge parameters made in the PK-4 chamber in the absence of dust [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, we include the effect of particle charge decrease as compared to the charge of an isolated particle, which is sometimes called "the charge cannibalism" [52,53]. Using (24) we obtain for this point…”
Section: Analysis Of Experiemntal Datamentioning
confidence: 99%
“…Although double layers have been mostly studied for collisionless plasmas, they also appear in collisional plasma (both current-carrying and current-free); examples are the current carrying DL in the cathode region of DC (direct current) discharges with two field reversals in the negative glow and Faraday dark space [37] and in the anode region of DC discharges [38]; the positive column of DC discharges in a constricted tube shows the formation of a DL often associated with the appearance of standing striations near the tube constriction [39,40]. The DL is also found in hollow cathode collisional discharges in which the anode is placed in a separate vacuum vessel communicating with the discharge chamber through an orifice [41].…”
Section: Introductionmentioning
confidence: 99%